Prospects for the Development of the National Social Insurance System - Hamraeva, F. (Research Parks Publishers, 2023)
This article covers the areas of development of the social insurance sector in Uzbekistan through digitalization, the prospects for using the experience of foreign countries in the introduction of digital technologies in the field.